2007
DOI: 10.1513/pats.200605-110jg
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Lung Transplant Rejection by Microarray Analysis

Abstract: Gene expression microarrays can estimate the prevalence of mRNA for thousands of genes in a small sample of cells or tissue. Organ transplant researchers are increasingly using microarrays to identify specific patterns of gene expression that predict and characterize acute and chronic rejection, and to improve our understanding of the mechanisms underlying organ allograft dysfunction. We used microarrays to assess gene expression in bronchoalveolar lavage cell samples from lung transplant recipients with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…Recent advances in genetic information using high throughput microarray analysis has revealed that there are quite different transcriptome patterns according to the rejection status after solid organ transplantation (5)(6)(7)(8). We already revealed that small bowel allografts undergoing ACR show distinct mRNA expression profiles involving immune, inflammatory and apoptosis genes reflect the histopathological changes in bowel biopsies and provided novel insights into these pathways operative in alloreactive inflammation (9).…”
Section: Introductionmentioning
confidence: 93%
“…Recent advances in genetic information using high throughput microarray analysis has revealed that there are quite different transcriptome patterns according to the rejection status after solid organ transplantation (5)(6)(7)(8). We already revealed that small bowel allografts undergoing ACR show distinct mRNA expression profiles involving immune, inflammatory and apoptosis genes reflect the histopathological changes in bowel biopsies and provided novel insights into these pathways operative in alloreactive inflammation (9).…”
Section: Introductionmentioning
confidence: 93%
“…14 Records of transbronchial lung biopsies with graded acute rejection and infections 15 were combined into the event list. The absence of events was determined by the lack of evidence of event occurrence.…”
Section: Datasetsmentioning
confidence: 99%
“…(Madsen et al 2010) A 2007 study by Lande et al describes the use of microarray analysis to observe relative gene expression levels of cytokines thought in be involved in acute rejection in the BAL fluid of AR patients. (Lande et al 2007) …”
Section: Biomarkers Of Acute Rejectionmentioning
confidence: 99%